2016
DOI: 10.1681/asn.2014100986
|View full text |Cite
|
Sign up to set email alerts
|

Mesencephalic Astrocyte–Derived Neurotrophic Factor as a Urine Biomarker for Endoplasmic Reticulum Stress–Related Kidney Diseases

Abstract: Endoplasmic reticulum (ER) stress and disrupted proteostasis contribute to the pathogenesis of a variety of glomerular and tubular diseases. Thus, it is imperative to develop noninvasive biomarkers for detecting ER stress in podocytes or tubular cells in the incipient stage of disease, when a kidney biopsy is not yet clinically indicated. Mesencephalic astrocyte-derived neurotrophic factor (MANF) localizes to the ER lumen and is secreted in response to ER stress in several cell types. Here, using mouse models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 30 publications
4
64
0
Order By: Relevance
“…We and others have shown that it manifests as extensive tubular dilation, epithelial flattening, tubular basement membrane denudation, and loss of brush borders in proximal tubules, which peaks between 4 and 5 days after injection (21,29). In comparison, glomeruli and other organs are spared (21,29). We have also shown that, despite normal renal function and the absence of conspicuous histologic changes on day 1 after TM injection, multiple ER stress response genes including BiP, CHOP, MANF and ER degradation-enhancing α-mannosidase-like protein (EDEM) are upregulated (21).…”
Section: Creld2 Is a Urinary Biomarker For Detecting Podocyte Er Strementioning
confidence: 74%
See 3 more Smart Citations
“…We and others have shown that it manifests as extensive tubular dilation, epithelial flattening, tubular basement membrane denudation, and loss of brush borders in proximal tubules, which peaks between 4 and 5 days after injection (21,29). In comparison, glomeruli and other organs are spared (21,29). We have also shown that, despite normal renal function and the absence of conspicuous histologic changes on day 1 after TM injection, multiple ER stress response genes including BiP, CHOP, MANF and ER degradation-enhancing α-mannosidase-like protein (EDEM) are upregulated (21).…”
Section: Creld2 Is a Urinary Biomarker For Detecting Podocyte Er Strementioning
confidence: 74%
“…In comparison, glomeruli and other organs are spared (21,29). We have also shown that, despite normal renal function and the absence of conspicuous histologic changes on day 1 after TM injection, multiple ER stress response genes including BiP, CHOP, MANF and ER degradation-enhancing α-mannosidase-like protein (EDEM) are upregulated (21). We further investigated whether CRELD2 was induced in ER-stressed renal tubules.…”
Section: Creld2 Is a Urinary Biomarker For Detecting Podocyte Er Strementioning
confidence: 98%
See 2 more Smart Citations
“…MANF is an ER-localized protein that is secreted upon ER stress [33] and implicated as a marker and therapeutic of neurodegeneration [3436]. Recently MANF’s potential as a disease biomarker has been investigated in both type I diabetes and kidney disease [37, 38]. Both found increased levels of MANF in serum and urine in disease-associated samples, respectively.…”
Section: Discussionmentioning
confidence: 99%